Deep-Dive Terraform on Azure automated delivery and deployment of Azure solutions - Modi, Ritesh (Apress L.P., 2021)
Get started with the foundations of Infrastructure as Code and learn how Terraform can automate the deployment and management of resources on Azure. This book covers all of the software engineering practices related to Terraform and Infrastructure as Code with Azure as a cloud provider. The book starts with an introduction to Infrastructure as Code and covers basic concepts, principles, and tools, followed by an overview of Azure and Terraform that shows you how Terraform can be used to provision and manage Azure resources. You will get started writing multiple Terraform scripts and explore its various concepts. Author Ritesh Modi takes a deep dive into Terraform and teaches you about deployment and multiple resource creation using loops. Writing a reusable script using modules is discussed as well as management and administration of secrets, sensitive data, and passwords within Terraform code. You will learn to store and version Terraform scripts and know how Terraform is used in Azure DevOps pipelines. And you will write unit and integration tests for Terraform and learn its best practices. The book also highlights and walks through the Terraform Azure Provider and shows you a simple way to create a new Terraform provider. After reading this book, you will be able to write quality Terraform scripts that are secure by design, modular, and reusable in Azure. You will: Understand implementation within infrastructure and application deployments Provision resources in Azure using Terraform Use unit and integration testing Explore concepts such as local vs remote, importing state, workspaces, and backends.